Pengembangan Platform Quizalize Terintegrasi Google Classroom sebagai Media Pembelajaran Bahasa Indonesia - Titin Tohiroh (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
This study aims to determine the advantages of the Quizalize platform, describe the form of development of Quizalize integrated with Google Classroom, and find out respondents’ responses to the Quizalize platform integrated with Google Classroom as an Indonesian Language Learning Media. This study uses a qualitative and quantitative approach. The method used is a questionnaire or survey method. The result of this study are advantages of the Quizalize platform, namely being able to use material and quizzes from other teachers, being able to provide follow-up on the evaluations carried out by students, and being able to print quizzes in the form of question papers. Quizalize platform development: 1) create Indonesian online classes, 2) create activities in online classes, 3) create quizzes or evaluations of Indonesian language learning, 4) create classes and quizzes in Quizalize integrated with Google Classroom. In addition, the results of the questionnaire that were made showed that the Quizalize media was effective, meaningful, interesting, quite easy to use, and helped in understanding Indonesian language learning.